2021
DOI: 10.7326/m21-1577
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Vaccine Effectiveness in a High-Risk National Population in a Real-World Setting

Abstract: Data are urgently needed on the real-world effectiveness of the currently administered COVID-19 vaccines. This case–control study evaluated the short-term effectiveness of currently administered vaccines in preventing confirmed SARS-CoV-2 infection among veterans receiving care in the U.S. Department of Veterans Affairs health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
86
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 21 publications
(14 reference statements)
9
86
2
2
Order By: Relevance
“…Differences in characteristics between recipients of the two vaccines might explain this finding, but similar results were also found in another Canadian province 36. Findings were, however, inconsistent in other studies that compared vaccine effectiveness between products after one dose; some found a trend towards higher effectiveness against infection using mRNA-1273,3738 whereas others found no difference 3940. However, the populations in each of these studies were more homogeneous than ours (eg, adults aged ≤40 years, healthcare workers, veterans).…”
Section: Discussioncontrasting
confidence: 82%
“…Differences in characteristics between recipients of the two vaccines might explain this finding, but similar results were also found in another Canadian province 36. Findings were, however, inconsistent in other studies that compared vaccine effectiveness between products after one dose; some found a trend towards higher effectiveness against infection using mRNA-1273,3738 whereas others found no difference 3940. However, the populations in each of these studies were more homogeneous than ours (eg, adults aged ≤40 years, healthcare workers, veterans).…”
Section: Discussioncontrasting
confidence: 82%
“…However findings were inconsistent in other studies that compared the effectiveness between products after one dose; some found a trend towards higher VE against infection in mRNA-1273 recipients, [37,38] whereas others found no difference. [39,40] However for each, their study populations were more homogeneous than ours (e.g., adults aged ≤40 years, healthcare workers, veterans). Our analysis also reflects extant evidence that effectiveness increases to very high levels after the second dose, even in older adults against symptomatic infection[16] and COVID-19-associated hospitalizations.…”
Section: Confidential -Not For Distribution 24 Jul 2021mentioning
confidence: 83%
“…BNT162b2 demonstrated strong protection against symptomatic and severe disease in clinical trials and the real world setting during early phases of the vaccine rollout internationally. 3,5,8,9,[38][39][40][41] We have now entered an era in which the vaccine durability, both over time and in the face of a rapidly evolving landscape of SARS-CoV-2 variants, must be continuously evaluated. This study constitutes an early signal that protection against symptomatic infection wanes over time after BNT162b2 vaccination.…”
Section: Discussionmentioning
confidence: 99%